Engagement of Facilities Management in Design Stage through BIM: Framework and a Case Study. (2nd May 2013) - Wang, Ying; Wang, Xiangyu; Wang, Jun; Yung, Ping; Jun, Guo
Abstract : Considering facilities management (FM) at the early design stage could potentially reduce the efforts for maintenance during the operational phase of facilities. Few efforts in construction industry have involved facility managers into the design phase. It was suggested that early adoption of facilities management will contribute to reducing the needs for major repairs and alternations that will otherwise occur at the operational phase. There should be an integrated data source providing information support for the building lifecycle. It is envisaged that Building Information Modelling (BIM) would fill the gap by acting as a visual model and a database throughout the building lifecycle. This paper develops a framework of how FM can be considered in design stage through BIM. Based on the framework, the paper explores how BIM will beneficially support FM in the design phase, such as space planning and energy analysis. A case study of using BIM to design facility managers' travelling path in the maintenance process is presented. The results show that early adoption of FM in design stage with BIM can significantly reduce life cycle costs.